(untitled) (Revista de História Regional, 2025)
The objective of this article is to analyze the trajectory of rural workers throughout their daily lives after wage labor in oil palm farming. To this end, we focused on their interactions within their families and communities. The research was conducted through a case study in the rural village of Belenzinho in the municipality of Acará, in northeastern Pará, between 2021 and 2023. We focused on direct observation, recording informal conversations, and interviews using semi-structured questionnaires with 18 workers who were experiencing their post-work as wage laborers in oil palm farming. We based our research on the concepts of daily life and rural work. The main conclusions show that the moments lived in the community and family are intensified after they have worked as wage laborers in oil palm farming. The workers assume and resume their work as family farmers and combine the knowledge acquired in oil palm farming as a way to remain in their place of origin and earn potential financial returns.